Specifics of Cultural-Civilization Identity Development in the Frontier Regions of Russia and Ukraine: Diagnostic Problems - Babintsev, Valentin P.; Gaidukova, Galina N.; Serkina, Yana I.; Pastyuk, Aleksandr V. (Journal of History Culture and Art Research, 2017)
This study analyzes the process of cultural and civilizational identity development in the border regions of Russia and Ukraine. The definition of a cultural-civilizational identity as a kind of macrosocial supra-ethnic identity is presented. A cultural-civilizational identity is a structure of self-consciousness that connects subjectively realized and experienced values, state and cultural symbols, attitudes, relations, assessments and norms of a supra-ethnic community. They prove that in order to understand the content of cultural and civilizational identity development in the border regions of Russia and Ukraine, the concept of political and cultural delimitation has a heuristic potential according to which the process of definition and delineation of adjacent geopolitical entity. This process consists in the development and distribution of stable notions about the specifics of their political and cultural systems among population. According to the materials of empirical study conducted in the border regions of Russia and Ukraine, (n = 1000, 2015), it is argued that the identification processes in the border regions of Russia and Ukraine do not primarily stimulate the restoration of the former high level of social space homogeneity. They separate more than unite the people of the borderland close by their cultural characteristics. The concept of identification process monitoring is proposed in the border regions of Russia and Ukraine.